Dynamic Modeling of Fuel Cells for Applications in Aviation - Niclas A. Dotzauer (Engineering Proceedings, 2025)
In the development of more electric aircraft, hydrogen powered fuel cells are one possible solution to progress towards emission reductions in aviation. Currently, there are numerous concepts for integrating fuel cells into future aircraft. The goal of this work was to develop a dynamic fuel cell model for simulations of the powertrain. The Modelica language together with the ThermoFluidStream (TFS) library from the German Aerospace Center (DLR) provided a suitable framework. The fuel cell model takes into account the electrochemical as well as thermodynamic behavior. Hence, the proposed multi-physics model allows simulating the whole fuel cell system, from the hydrogen tank to the electric grid. Under certain simplifications, this enables performing mission simulations of the complete powertrain of future aircraft. As such, polymer electrolyte membrane (PEM) fuel cells and solid oxide fuel cells (SOFC) were considered. The fuel cell models are checked for plausibility in a simple test case against data from the literature. Furthermore, two setups of possible applications are introduced: one for each fuel cell type, which come from two projects. The preliminary control systems of these architectures are presented. Afterwards, the first results of the fuel cell systems are discussed. These results show that the models ran robustly in various environments and operational states. They provided the desired accuracy to predict the behavior of a fuel cell, while maintaining low CPU times and being capable of enabling real-time simulations in the future.